2015
DOI: 10.1073/pnas.1515968112
|View full text |Cite
|
Sign up to set email alerts
|

Subunit composition of a DEG/ENaC mechanosensory channel of Caenorhabditis elegans

Abstract: Caenorhabditis elegans senses gentle touch in the six touch receptor neurons (TRNs) using a mechanotransduction complex that contains the pore-forming degenerin/epithelial sodium channel (DEG/ENaC) proteins MEC-4 and MEC-10. Past work has suggested these proteins interact with the paraoxonase-like MEC-6 and the cholesterol-binding stomatin-like MEC-2 proteins. Using single molecule optical imaging in Xenopus oocytes, we found that MEC-4 forms homotrimers and MEC-4 and MEC-10 form 4:4:10 heterotrimers. MEC-6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 42 publications
2
46
1
Order By: Relevance
“…3), indicating that both MEC-2 and MEC-6 are dispensable for this response. This is not surprising as MEC-2 and MEC-6 do not contribute to the channel's pore (7). In contrast, the LSS response was largely abolished in channels lacking MEC-10.…”
Section: Mec-10 Is Required For Lss-mediated Channel Activation-mentioning
confidence: 86%
“…3), indicating that both MEC-2 and MEC-6 are dispensable for this response. This is not surprising as MEC-2 and MEC-6 do not contribute to the channel's pore (7). In contrast, the LSS response was largely abolished in channels lacking MEC-10.…”
Section: Mec-10 Is Required For Lss-mediated Channel Activation-mentioning
confidence: 86%
“…In the DA sensory neurons, PPK1 functions with PPK26 as part of a highly-expressed mechanotransduction channel (Gorczyca et al, 2014; Guo et al, 2014; Mauthner et al, 2014). The third subunit of the DA-neuron PPK1-containing mechanotransduction channel has yet to be identified, although it remains possible that the DA-neuron channel is not heterotrimeric (Chen et al, 2015). By characterizing a novel PPK1 containing ENaC channel in the context of PHP, we provide direct evidence that different PPK subunit assemblies can generate channels with very different properties and unique physiological roles in Drosophila neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, MEC-4(A713T) [denoted MEC-4(d)] requires coexpression with stomatin-like protein MEC-2 and paraoxonase-like protein MEC-6 to achieve robust currents in oocytes (6,(11)(12)(13)19). MEC-4 homologous subunit MEC-10 is also part of the channel complex in vivo (22,34), however, recent work has shown that it is important but not required for channel function (assayed as a response to gentle touch, the behavior mediated by the MEC-4 channel).…”
Section: Neurotoxic Deg/enac Channels Unc-8(d) and Mec-4(d)mentioning
confidence: 99%
“…MEC-4 homologous subunit MEC-10 is also part of the channel complex in vivo (22,34), however, recent work has shown that it is important but not required for channel function (assayed as a response to gentle touch, the behavior mediated by the MEC-4 channel). Moreover, MEC-10 appears to be localized only in the cell body and proximal dendrite, suggesting that MEC-4 homomultimeric channels are present in vivo at cellular locations where MEC-10 is absent (10,13). For these reasons, we decided to focus our analysis on MEC-4(d) ϩ MEC-2 ϩ MEC-6.…”
Section: Neurotoxic Deg/enac Channels Unc-8(d) and Mec-4(d)mentioning
confidence: 99%